Design and optimization of BNi-2+CoCrNi composite interlayer for GH5188 superalloy TLP bonding - Wei Guo; Jingru Xin; Long Gao; Xinlei Ding; Peilong Fan; Xinrong Li; Bosong Tao; Jiangtao Xiong; Jinglong Li (Journal of Materials Research and Technology)
Transient liquid phase (TLP) bonding of GH5188 superalloy was achieved using composite interlayers of BNi-2 and CoCrNi medium-entropy alloy (MEA) powders at 1190 °C/60 min. The critical role of CoCrNi MEA content was systematically investigated. At 0.5–1 wt.%, CrB precipitates dominated the joint microstructure, while 2 wt.% induced γ-matrix coexistence with Si–B compounds. The peak shear strength of 878 MPa (88.4 % of the base metal) was attained at 0.5 wt.% CoCrNi MEA, the interlayers with higher contents triggered fracture mode transitions from ductile (0.5 wt.%) to mixed (1 wt.%) and ultimately brittle failure in the athermal solidification zone (ASZ) at 2 wt.%. Mechanistic analysis revealed that excessive CoCrNi MEA addition (>1 wt.%) impaired interlayer wettability, promoting void nucleation. This work establishes a compositional design framework for high-performance TLP bonding of refractory superalloys in extreme environments.